Growth Performance of Early Finishing Gilts as Affected by Different Net Energy Concentrations in Diets - Lee, Gang Il (Asian-Australas J Anim Sci, 2015)
The objectives of the current experiment were to study the response of the growth performance of early finishing gilts to different net energy (NE) concentrations in diets, and to compare the NE values of diets between calculated NE values and measured NE values using French and Dutch CVB (Centraal Veevoederbureau; Central Bureau for Livestock Feeding) NE systems. In a metabolism trail, the NE concentrations in five diets used for the growth trial were determined based on digestible nutrient concentrations, digestible energy, and metabolizable energy using a replicated 5×5 Latin square design with 10 barrows (initial body weight [BW], 39.2±2.2 kg). In a growth trial, a total of 60 early finishing gilts (Landrace×Yorkshire; initial BW, 47.7±3.5 kg) were allotted to five dietary treatments of 8.0, 9.0, 10.0, 11.0, and 12.0 MJ NE/kg (calculated, as-is basis) with 12 replicate pens and one pig per pen in a 42-d feeding experiment. The NE and amino acid (AA) concentrations in all diets were calculated based on the values from NRC (2012). Ratios between standardized ileal digestible AA and NE concentrations in all diets were closely maintained. Pigs were allowed ad libitum access to feed and water. Results indicated that calculated NE concentrations in diets (i.e., five dietary treatments) were close to measured NE concentrations using French NE system in diets. The final BW was increased (linear and quadratic, p<0.05) with increasing NE concentrations in diets. Furthermore, average daily gain (ADG) was increased (linear and quadratic, p<0.01) with increasing NE concentrations in diets. There was a quadratic relationship (p<0.01) between average daily feed intake and NE concentrations in diets. Feed efficiency (G:F) was also increased (linear, p<0.01) as NE concentrations in diets were increased. The NE intake per BW gain (kcal NE/kg of BWG) was increased (linear, p<0.01) with increasing NE concentrations in diets that were predicted from both French and Dutch CVB NE systems. Linear regression indicated that predictability of daily NE intake from the BW of pigs was very low for both French (R(2), 0.366) and Dutch CVB (R(2), 0.374) NE systems. In conclusion, increasing NE concentrations in diets increase BW, ADG, G:F, and NE intake per BW gain of early finishing gilts. The BW of early finishing gilts is not a good sole variable for the prediction of daily NE intake.